Positron Emission Tomography/Computed Tomography with Gallium-68–labeled Prostate-specific Membrane Antigen Detects Relapse After Vascular-targeted Photodynamic Therapy in a Prostate Cancer Model - Alvim, Ricardo (Eur Urol Focus, 2019)
BACKGROUND: Evaluating the efficacy of focal therapy for prostate cancer is limited by current approaches and may be improved with biological imaging techniques. OBJECTIVE: We assessed whether positron emission tomography/computed tomography with gallium-68–labeled prostate-specific membrane antigen ((68)Ga-PSMA PET/CT) can be used to predict relapse after vascular-targeted photodynamic therapy (VTP). DESIGN, SETTING, AND PARTICIPANTS: A total of 1 × 10(6) LNCaP cells were grafted subcutaneously in the flanks of 6–8–wk-old SCID mice. Of 24 mice with measurable tumors 6 wk after tumor implantation, 20 were treated with VTP (150 mW/cm(2)) to ablate the tumors. Blood prostate-specific antigen (PSA) levels were assessed, and (68)Ga-PSMA PET/CT images were performed 1 d before VTP and 1 and 4 wk after. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Local tumor relapse was evaluated by histology, and tumors were analyzed by prostate-specific membrane antigen (PSMA) and PSA immunohistochemistry. T tests and Kruskal-Wallis tests were used to determine significance. RESULTS AND LIMITATIONS: Four weeks after VTP, 11 (65%) mice had complete responses and six (35%) had tumor relapses confirmed by histology (hematoxylin and eosin, and PSMA immunohistochemistry). All mice with local relapse had positive (68)Ga-PSMA PET/CT findings 4 wk after VTP; all complete responders did not. One week after VTP, the relapse detection sensitivity of (68)Ga-PSMA PET/CT was 75%, whereas the sensitivity of PSA was only 33%. Compared with controls, relapsed tumors had a three-fold reduction in the number of cells with strong PSA staining by immunohistochemistry (1.5% vs 4.5%; p = 0.01). CONCLUSIONS: In a preclinical prostate cancer model, we show that (68)Ga-PSMA PET/CT can identify and predict relapse earlier than blood PSA level. These findings support further testing in clinical trials. PATIENT SUMMARY: Positron emission tomography/computed tomography with gallium-68–labeled prostate-specific membrane antigen may be used to follow and evaluate treatment outcomes in men who receive focal therapy for prostate cancer.